6-Methyl-ideneandrost-4-ene-3,17-dione - Andrade, L. C. R. (2012)
In the title compound, C(20)H(26)O(2), which is the 6-methyl-ene derivative of androstenedione and a synthetic percursor of exemestane, the steroid A ring approximates to a sofa (or envelope) conformation, with the methyl-ene group adjacent to the link to the B ring lying out of the plane of the other atoms. The B and C rings have slightly flattened chair conformations and the D ring is an envelope, with the CH group forming the flap. In the crystal, mol-ecules are linked by two distinct C-H⋯O hydrogen bonds, involving acidic H atoms close to C=C and C=O double bonds.